Hong–Ou–Mandel Interference on an Acousto-Optical Beam Splitter - Piotr Kwiek (Optics)
This paper presents the results of theoretical and experimental investigations of a Hong–Ou–Mandel interferometer in which an optical beam splitter is replaced by an ultrasonic wave. The ultrasonic wave acts as an acousto-optical beam splitter for light, which is based on the phenomenon of Bragg diffraction on an ultrasonic wave. The Doppler effect was considered in the theoretical considerations and confirmed experimentally. It has been shown theoretically and experimentally that the Doppler effect changes the frequency of two-photon states at the outputs of an acousto-optical beam splitter. The frequency of the two-photon state in the positive diffraction order is increased by the frequency of the ultrasonic wave, whereas in the negative diffraction order, it is reduced by the frequency of the ultrasonic wave. It should be emphasized that there are no states <semantics><mfenced open="|" close="|" separators="|"><mfenced open="" close="⟩" separators="|">1</mfenced>1</mfenced><mfenced open="" close="⟩" separators="|">1</mfenced>2</semantics> in the outputs (diffraction orders), which disappear as a result of Hong–Ou–Mandel interference; consequently, the probability of detecting coincidences of photons between the plus first and minus first diffraction orders is zero, as it occurs in the Hong–Ou–Mandel interferometer. The frequency difference between the two-photon states at the outputs of the acousto-optical beam splitter was confirmed by recording the two-photon beat phenomenon. The obtained results changed the current view that the Doppler effect caused by ultrasonic waves can be neglected in the interaction of correlated pairs of photons with ultrasonic waves.